(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Intravenous induction agents play a vital role in maintaining hemodynamic stability during general anesthesia. Propofol is commonly preferred because of its rapid onset and smooth recovery profile, although it frequently causes hypotension and cardiovascular depression. Etomidate is considered more hemodynamically stable and is often used in patients with compromised cardiovascular status. Aim: To assess and compare the hemodynamic changes and recovery profile following induction of general anesthesia using propofol and etomidate. Materials and Methods: A prospective comparative study was conducted among 120 adult patients undergoing elective surgeries under general anesthesia. Patients were randomly divided into two groups of 60 each. Group A received propofol 2 mg/kg intravenously, while Group B received etomidate 0.3 mg/kg intravenously for induction. Hemodynamic parameters including heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP) were recorded at baseline, after induction, and after intubation. Recovery profile and adverse effects were also evaluated. Results: Group B demonstrated significantly greater hemodynamic stability compared to Group A. The reduction in MAP after induction was significantly higher in Group A (p<0.001). Recovery time was shorter in Group A than Group B (p<0.05). Injection pain was more common in Group A, whereas myoclonus was observed predominantly in Group B. Conclusion: Etomidate provided superior hemodynamic stability during induction of general anesthesia, whereas propofol showed a faster recovery profile. Etomidate may be considered a safer induction agent in patients where cardiovascular stability is a major concern.